Isochronous systems - Calogero, F. (Oxford : Oxford University Press, 2008)
This book will be of interest to students and researchers working on dynamical systems, including integrable and nonintegrable models, with a finite or infinite number of degrees of freedom. It can be used as a textbook or as background reading for an undergraduate or graduate course.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Dynamics; System analysis; Differential equations